THE APPLICATION OF CLASSICAL MUSIC METHOD TO LEARNING BURNOUT ON ENGLISH LANGUAGE COURSE AT IAI AL AMANAH JENEPONTO - Sudharmono (Prodi Bimbingan Konseling Universitas Negeri Manado, 2023)
This study aims to determine whether the method of providing classical music in the learning process can reduce the level of boredom learning students on English language courses. The research method used a pre-experiment design approach to 30 research subjects who were even semester students (2) FY 2022/2023 at IAI Al Amanah Kab. Jeneponto. Data were collected using questionnaires and observations and then analyzed using descriptive statistical analysis and inferential statistical analysis of t-tests. The results showed that the application of classical music methods can reduce the level boredom learning students on English language courses.